(untitled) (Revista horizonte, 2022)
The evolution of higher education has led universities to rethink the way of teaching andevaluating, for which they have developed a process of curricular reform based on competencies characterized by being focused on student learning, which is how they have been implementednew and innovative teaching-learning strategies that demonstrate not only the theoretical content but the development of abilities and skills that allow the student to put into practice clinical reasoning, problem solving and effective communication. Methodologically, as it is an Essay, a bibliographic search was conducted in Spanish and English in the database; Scielo, Scopus, PubMed, Redalyc, Education (JSTOR). The purpose of this paper is to determine the theoretical bases and importance of the application of clinical simulation in learning activities.